Respuesta :

9x = -90
X = -10

-10y = -90
Y= 9
9x-10y = -90
 For this case what you should do is see the intersections with each of the axes and then join the ordered pairs.
 We have then:
 For the x axis:
 
y = 0
 Substituting in the equation:
 9x-10 (0) = - 90
 9x-0 = -90
 x = -10
 For the y axis:
 
x = 0
 Substituting in the equation:
 9 (0) -10y = -90
 0-10y = -90
 y = 90/10
 y = 9
 We graph the ordered pairs:
 (x1, y1) = (- 10, 0)
 (x2, y2) = (0, 9)
 Answer:
 See attached graph.
Ver imagen carlosego